1387 Impact of Perinatal Nutrition on Kidney Function at Five Years in Very Low Bieth-Weight Children. (October 2012) - Vieux, R; Galu, S; Guillemin, F; Hascoet, JM
Abstract : Aim: To determine the impact of perinatal factors on renal function in five year-old preterm-born children. Material and Methods: Prospective longitudinal study of preterm-born children from birth to five years of age, and five year-old full-term controls. Renal function measured in the neonatal period and at five years. Primary outcome was renal function at five years: blood pressure (BP), estimated glomerular filtration rate (eGFR), albuminuria. Multivariate analysis was performed with multiple linear regression models. Results: 168 children included aged 5.1±0.1 years. 133 preterm-born children, born: 29.2±1.4 weeks gestation; 35 full-term children aged five. Systolic BP (sBP) was 97.5±7.1 mmHg in preterm-born children versus 92.2±8.1 mmHg in full-term controls, p=0.0001. In preterm-born children, sBP increased by (β±σ): 2.2±1.0 mmHg for each gram/kg increase in proteins/day on day 28, and decreased by –3.0±1.4 in case of bronchopulmonary dysplasia, after adjustment on gender and height at five years. eGFR was 176.3±37.1 mL/min/1.73m² at five in preterm-born children. It was significantly decreased when children had presented hyaline membrane disease or necrotising enterocolitis, respectively (β±σ): –17.6±6.7 and –25.7±10.4 mL/min/1.73m². eGFR at five was not associated with neonatal nutrition. 14.4% preterm-born children had an albumin ratio >2 mg/mmol vs. 11.1% full-terms, p=0.7. Renal volume, absolute or relative, at five years was negatively correlated to protein intakes from day 14 onwards in the neonatal period: R= –0.69, p=0.006. Conclusion: Protein intakes in the neonatal period are associated to an increased BP and decreased renal volume in five year-old preterm-born children.